A Survey on Frequency Reconfigurable Antenna for Wireless Applications - K. , Jayamani; Rahulkrishnan; S. , Aishwarya Nachiya; R. , Arjun Raj; C. , Atchaya (International Journal of Psychosocial Rehabilitation, 2020)
Wireless communication technology has experienced exponential growth over the past years. The growth of technologies has led to increased demand for the antenna, which could serve for different wireless applications. Reconfigurable antennas are the subject of study in much research, as they play an important role in smart and adaptive systems in wireless networks. A reconfigurable antenna provides the advantage of combining multiple functions in a single antenna. Reconfigurable antennas are able to dynamically modify their frequency and radiation properties. Different reconfiguration techniques are used to modify the properties of an antenna. They are popular due to their low cost, compact size, and light weight. Various papers on frequency reconfigurable antennas are studied, and a comparative study is presented.